Capitalizing on the advantages of the Latin American EAP situation - Iliana A. Martínez (Ibérica, 2011)
This paper describes a situation that suggests an optimistic future for periphery scholars, particularly from Latin America. First it shows a positive evolution of publications in English in Latin America, which appears to be associated to the concomitant evolution of postgraduate programmes. Then, it is argued that such evolution could be improved by a form of EAP instruction that capitalizes on the special characteristics of the Latin American situation, particularly the highly specific needs of learners, the common Latinate L1, the possibility of having homogeneous groups in terms of fields, and the limited set of genres used by researchers in this context. Such features could be exploited to the learners' advantage through the use of authentic and specific materials. Both authenticity and specificity will increase motivation and reduce comprehension problems, while allowing participants to contribute their knowledge of science to the course.